Legal Certainty in the Implementation of Grant Land Deed to Grandchildren (Study of Decision Number: 357/PDT/2023/PT BDG.) - Budiarto, Rio (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
Land is a natural resource that is important for human life, both as a place to live and as a source of economic welfare. In Indonesia, the strategic role of land is regulated in Article 33 paragraph (3) of the 1945 Constitution which emphasizes that natural resources are controlled by the state for the prosperity of the people. However, not all individuals, such as minors, are considered capable of carrying out legal acts related to land ownership. Grants, as one way of transferring land ownership, are regulated in Article 1666 of the Civil Code, which states that grants are free gifts made while the grantor is still alive and must go through a notarial deed. This study examines a land grant dispute case in Cirebon Regency, where land was granted to a minor but was later sued by his grandmother who claimed ownership of the land with evidence of a receipt. This study raises two problem formulations: (1) the considerations of the Panel of Judges in deciding on the grant of a land deed to a grandchild, and (2) legal provisions related to the status of minors as recipients of grants. The research method uses a normative legal approach with secondary data analysis involving primary, secondary, and tertiary legal materials. The results of the study indicate that the decision of the Bandung High Court to annul the decision of the Sumber District Court was correct, upholding legal certainty and justice. In addition, minors do not have full legal capacity to receive land grants directly, so they require the consent of a legal guardian or parent. This regulation aims to protect children's rights and ensure that land management is carried out properly in accordance with applicable legal principles.